Modelling Of Potential Field Data For Shallow Thermal And Crustal Structure Beneath Peninsular Malaysia - Yaro, Usman Yahaya (2022)
This thesis has taken advantage of the global compilation of potential field data to derive the first regional thermal structure as well as the most resolved crustal thickness model for the entire Peninsular Malaysia and neighbouring regions. Bore-hole heat flow data can provide the most precise information about the thermal structure of the crust, but these measurements are extremely difficult to obtain (expensive, sparse, and limited to shallow depths). The depth to bottom of magnetic sources (DBMS) has traditionally been used as alternative to surface heat flow data. In this study, DBMS are derived assuming random uncorrelated and fractal magnetisation models. DBMS using fractal distribution of sources (~ 17 – 46 km with a mean of 29 km) are found to be lower than the values computed using conventional random method (29 – 67.4 km with a mean value of 49.3 km) and reasonably well while considering other tectonic and geophysical constraints. Despite, the differences in the derived DBMS for the two methods, visual inspection and cross plots shows that they are linearly correlated, and they have the same pattern and trends. Crustal thickness for the study area varies from ~ 27.4 – 34.6 km with an average of 30.8 km. A comparison between the derived DBMS and crustal thickness shows that the upper mantle beneath the west Sumatra, Singapore, Malay basin, NW Peninsular Malaysia, and southern Thailand are significantly magnetised. The presence of magnetic upper mantle point to the stability of these regions attributable to low heat flow, geothermal gradient, and serpentinization.